Respostas
respondido por:
0
An= A₁ + (n-1) * r
149= 9 + (n-1) * 4
149= 9 + 4n-4
149-9+4= 4 n
144= 4n
n=36 termos
149= 9 + (n-1) * 4
149= 9 + 4n-4
149-9+4= 4 n
144= 4n
n=36 termos
Fabinho157:
Vlw João ajudou MT
respondido por:
1
Primeiro encontramos sua razão :
r = a2 - a1
r = 13 - 9
r = 4
Agora basta usar a fórmula :
An = a1 + ( n - 1) . r
149 = 9 + ( n - 1) . 4
149 = 9 + 4n - 4
149 = 4n + 5
149 - 5 = 4n
4n = 144
n = 144/4
n = 36 termos tem a PA. ok
r = a2 - a1
r = 13 - 9
r = 4
Agora basta usar a fórmula :
An = a1 + ( n - 1) . r
149 = 9 + ( n - 1) . 4
149 = 9 + 4n - 4
149 = 4n + 5
149 - 5 = 4n
4n = 144
n = 144/4
n = 36 termos tem a PA. ok
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás